Lactate to albumin ratio as a prognostic marker for all-cause mortality in patients with venous thromboembolism: a retrospective cohort study - Huang, Yun; Zhang, Chunyan; Mei, Jun; Li, Meiqiu; Wu, Yingxin; Xiang, Xia (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe lactate to albumin ratio (LAR) may serve as a prognostic marker. This study evaluated its association with clinical outcomes in patients with venous thromboembolism (VTE).MethodsWe performed a retrospective cohort analysis using data from the MIMIC-IV 3.1 database, including 4,181 patients diagnosed with VTE. The primary outcomes were 30-day and 365-day all-cause mortality. Cox proportional hazards models assessed the relationship between LAR and mortality. Restricted cubic spline (RCS) analysis examined the non-linear relationship. Kaplan–Meier (KM) survival curves were generated to compare outcomes across the LAR groups.ResultsAmong the 1,992 patients included in the study, mortality rates at 30 and 365 days were 19.58% and 22.69%, respectively. Elevated LAR levels were significantly associated with increased mortality at both time points (P < 0.001). The hazard ratio (HR) for 30-day mortality was 2.02 (95% CI: 1.42–2.88), while for 365-day mortality, it was 1.83 (95% CI: 1.33–2.52). Receiver operating characteristic (ROC) analysis demonstrated that LAR + SOFA had an area under the curve (AUC) of 0.670 for 30-day mortality and 0.664 for 365-day mortality. Subgroup and sensitivity analyses confirmed the robustness of these findings across different clinical scenarios.ConclusionsElevated LAR is significantly associated with increased mortality in VTE patients. LAR can be used as a potential indicator for assessing the short-and long-term risk of mortality in such patients.